PENGARUH PEMBERDAYAAN PEGAWAI DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI DENGAN MEDIASI IKLIM ORGANISASI PADA SEKRETARIAT DAERAH KABUPATEN PEKALONGAN - Isrorina, Isrorina; Setyowati, Widhy (Jurnal Ilmiah Telaah Manajemen, 2009)
This Research havea purpose to explain the influence at enableness of officer And job characteristic to officer performance mediation by Climate Organisation at office of Secretariat Pekalongan Regency. Researchpopulation is public servant of Civil at Secretariat Pekalongan Regency, while sample use the technique of purposive sampling. Method data collecting by using quesioner which passed to a responder. Examination toresearch instrument done with the validity test ( analyse the factor) and test the reliabilitas with the coefficient alpha of appliance to statistic test by multiple regression analysis regresi, test the t, test R2 and mediation test. Result of research indicate that the officer enableness have an effect is positive and signifikan to organizational climate and performance. Job characteristic have an effect on positive and signifikan to organizational climate. Job characteristic have an effect on the negativity but don,t signifikan to officer performance, while organizational climate have an effect on positive to performance but no signifikan.Keyword : Officer Enableness, Job Characteristic, Organizational Climate, Performance